Cultivating a Culture of Innovation: The Experience of Al Salam Private School in Dubai, United Arab Emirates - Santos, Mark Rey (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Innovation, being one of the initiatives of the UAE, has been mandated to be promoted and cultivated in all government sectors including education. In response to the mandate, schools incorporated innovation into their system and operation. Al Salam Private School, in its existence for more than 30 years, has made a lot of innovative steps to address the call and demands of the time. The culture of innovation in Al Salam Private School may already be existing, but in order to know how to move forward, an assessment was made to determine the perception of the staff. The Six Building Blocks of an Innovative Culture instrument of Rao and Weintraub (2013) was modified to suit and fit the need of the survey. The survey revealed that overall, the culture of innovation in Al Salam Private School is to a great extent. Specifically, the culture of innovation in terms of values, behaviors, climate, and processes are to a great extent while resources and success are to a moderate extent. The focus areas derived from the three least rated elements in the survey are: having good incentive systems which recognize and reward innovation, rewarding people for participating in potentially risky opportunities, irrespective of the outcome, and having inspiring physical spaces for staff to collaborate, be creative and engage in innovative practice. Three emerging themes were extracted from the interview with the key informants, and these are incentives and recognition, risk-taking activities, and collaborative and inspiring space. These themes were consistent with the focus areas derived from the survey. From the integration of the quantitative and qualitative analysis, an eidetic model of the culture of innovation was developed. The three pillars of the model served as the key priority areas in the crafting of the Innovation Plan.